As Steady as a Rock! Gaining Insight in Recruitment and Retention Among Primary School Children With Behavioural Problems in Sport Mix Club - Prevo, Lotte; Jansen, Maria; Van Kann, Dave; Kremers, Stef (Frontiers in Public Health, 2022)
The number of children dealing with behavioural problems is increasing. A major challenge in many health-supportive programmes is the recruitment and retention of these children. In the current study, Sport Mix Club (SMC), an approach to enhance socioemotional disorders of 4- to 12-year-old children through sport classes in municipality Vaals, the Netherlands, is used as an illustration. Where many studies faced difficulties getting and keeping children in their interventions, SMC overcame this challenge. Therefore, we decided to explore ‘What factors contribute to enhanced recruitment and retention procedures among children with behavioural problems in Sport Mix Club?’ A qualitative case study design using the analysis of the administrative logbook of the SMC coach and trainees, interviews with the SMC coach, trainees (n=2), school teachers (n=3) and parents of participating children (n=9), and four focus group interviews with children (n=13) were carried out. During the recruitment and retention of SMC, the human psychological need of relatedness seemed to be of crucial value. The fact that the SMC coach: 1) made efforts to become a familiar face for children, parents and community partners beforehand; 2) showed enthusiasm; and 3) placed her focus on having fun as opposed to the children’s problems, seemed to be decisive in the process of getting children to participate in SMC and retaining their participation.